What Explains Prevalence of Informal Employment in European Countries : The Role of Labor Institutions, Governance, Immigrants, and Growth - Hazans, Mihails (2012)
This paper looks into institutional and other macro determinants of prevalence of informal dependent employment, as well as informal self-employment, in European countries, using European Social Survey data on work without legal contract in on 30 countries, covering years 2004-2009. Consistently with theoretical predictions, quality of business environment has a significant negative impact on prevalence of both types of informal employment. The share of non-contracted employees is negatively affected by perceived quality of public services and positively related to economic growth. Informal self-employment is positively related to growth in Europe at large, as well as in Eastern and Southern Europe. The level of GDP per capita also has a positive impact on the prevalence of informal employment in Europe at large and within Eastern and Southern Europe, whilst an opposite effect is found in Western and Northern Europe. Other things equal, the share of non-contracted employees in the labor force across European countries increases with the minimum-to-average wage ratio, with union density, with the share of first and second generation immigrants, and with income inequality, but falls with stricter employment protection legislation (EPL) and higher tax wedge on labor. Thus it appears that in Europe at large, labor cost effects of EPL and taxes are weaker than their impact via perceptions of job security and law enforcement, along with tax morale and the income effect. Yet the EPL effect on informality is positive (i.e., cost-related) when either Eastern and Southern Europe or Western and Northern Europe are considered separately. Furthermore, within Western and Northern Europe, the minimum wage effect is negative, whilst within Eastern and Southern Europe, the union effect is negative; in both cases, we offer a supply side explanation.